Molybdenum and molybdenum alloy plate rolling oil and preparation method thereof

By rolling oil and molybdenum alloy plates composed of additives such as V2O5-COFS covering materials, the problem of single and lack of performance of the existing lubricant effects, realized low friction coefficients, good stability and efficient lubrication effects, improvement The production efficiency and product quality of the cold rolling process.

CN119372007APending Publication Date: 2025-01-28XI'AN UNIVERSITY OF ARCHITECTURE AND TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411493293.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

The existing molybdenum and molybdenum alloy cold-rolled lubricating oil has a single effect, which is difficult to meet the conditions of multiple working conditions, and is insufficient in oxidation resistance, corrosion resistance and clean dispersion properties.

Method used

Using basic oil, V2O5-COFS, oil-based, antioxidants, cleaning agents, dispersers, rust-proof and antid emulsion agents, molybdenum and molybdenum alloy plates, and use specific preparation methods to high temperature The stirring of the reaction kettle form a stable lubricant.

Benefits of technology

The low friction coefficient, good antioxidant, corrosion resistance and decentralized stability can be achieved. It can maintain clean and transparent in long -term use, reduce the number of spray times, improve rolling efficiency and product surface quality.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119372007A_ABST
    Figure CN119372007A_ABST
Patent Text Reader

Abstract

The invention discloses molybdenum and molybdenum alloy plate rolling oil and a preparation method thereof. The molybdenum and molybdenum alloy plate rolling oil is prepared from the following raw materials in parts by weight: 80.2 to 91.2 parts of base oil, 3 to 5 parts of a V2O5-COFs coating material, 1 to 3 parts of an oiliness agent, 0.5 to 1.0 part of an antioxidant, 1 to 3 parts of a clearing agent, 1 to 3 parts of a dispersing agent, 2 to 4 parts of an antirust agent and 0.3 to 0.8 part of a demulsifying agent. The rolling oil for rolling the pure molybdenum plate and the molybdenum-rhenium alloy plate is low in friction coefficient and good in oxidation resistance, corrosion resistance and dispersion stability. In the cold rolling process, continuous lubrication can be achieved by spraying the rolling oil once, the action range is large, the action time is longer, and the spraying frequency is reduced. When the rolling oil for rolling the pure molybdenum plate and the molybdenum-rhenium alloy plate is used for cold rolling, on one hand, the rolling deformation resistance can be reduced, the bearing capacity of equipment is reduced, and the service life of the equipment is prolonged; and on the other hand, rolling passes can be reduced, the rolling speed is increased, and the production efficiency of enterprises is greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lubricating materials, and in particular relates to a rolling oil for molybdenum and molybdenum alloy plates and a preparation method thereof. Background Art

[0002] Metallic molybdenum and its alloys have important applications in metallurgy, machinery, energy, electronic equipment manufacturing, aerospace and defense industries. With the development of industrial technology, the demand for molybdenum plates is increasing. As an essential material in the field of high-tech industries, whether it is used as a raw material for terminal application products or other deep-processing products, the precision and performance requirements of molybdenum plates will become higher and higher, requiring high dimensional accuracy, good plate shape and surface quality. The rolling process of molybdenum alloy plates goes through three stages: hot rolling, warm rolling and cold rolling. The hot rolling process of pure molybdenum plates usually does not require lubricating oil, and it can play a lubricating role by relying on a layer of oxide film formed by itself. In the cold rolling process, due to the low temperature, its own deformation resistance is large. Without the auxiliary effect of a good lubricant, it is difficult to form a product with high surface quality. For example, the probability of surface defects such as edge waves, edge cracks, and warping on the surface of the plate increases.

[0003] At present, most of the molybdenum and molybdenum alloy cold rolling lubricants on the market tend to be pure base oils, such as transformer oil, kerosene and other single components, with single effects, and it is difficult to meet the use conditions of multiple working conditions. For example, it can only be used at low speed and low load, and may not be used for high-speed rolling. Therefore, it is extremely necessary to develop rolling oils that meet the needs of multiple working conditions and meet the standards of anti-oxidation performance, anti-corrosion performance, and cleanliness and dispersion performance while meeting the basic use conditions. Summary of the invention

[0004] The first object of the present invention is to provide a rolling oil for molybdenum and molybdenum alloy plates, and the second object of the present invention is to provide a method for preparing the rolling oil.

[0005] The first object of the present invention is achieved in this way. A rolling oil for molybdenum and molybdenum alloy plates is composed of the following raw materials in parts by weight: 80.2~91.2 parts of base oil, 3~5 parts of V2O5-COFs coating material, 1~3 parts of oiliness agent, 0.5~1.0 parts of antioxidant, 1~3 parts of detergent, 1~3 parts of dispersant, 2~4 parts of rust inhibitor, and 0.3~0.8 parts of anti-emulsifier.

[0006] The second object of the present invention is achieved by the method for preparing the rolling oil for molybdenum and molybdenum alloy plates, which is achieved by the following steps: (1) Add base oil and V2O5-COFs coating material in a stainless steel high-temperature reactor according to the weight ratio, stir at a speed of 600 rpm / min for 1-2 hours in the temperature range of 120-150°C, stop heating, and continue stirring until the temperature drops to 70-80°C; (2) Add other raw materials in the reactor in order according to weight, maintain the temperature of the reactor at 70-80°C, and stir at a stirring rate of 600-800 rpm / min for 1-2 hours to obtain the target molybdenum and molybdenum alloy plate rolling oil.

[0007] The rolling oil of the present invention uses V2O5-COFs coating material as an additive. The V2O5 nanosphere has a large specific surface area. The active sites on the surface and inside of the sphere are activated by a surfactant template method, wherein the hydrophilic end of the surfactant is connected to the nanosphere, and the lipophilic end is connected to the COFs material, resulting in a stable adsorption effect, forming a cavity for storing lubricating oil. The COFs film material is connected by covalent bonds, and the structure is more stable. The pores are lipophilic, and the structure is adjusted and self-repaired very quickly while the coordination self-assembly is carried out, and it has strong universality. During the rolling process, the lubricating oil on the surface and inside of the sphere forms a continuous lubricating film under the action of the rolling force. As the rolling force increases, the porous nanosphere breaks, and the surface and inside of the formed nanosheet form a layered composite structure with the COFs film material, which further exerts a lubricating effect on the rolling process, which is beneficial to the improvement of the surface quality of the rolled plate and the rolling production efficiency. The experimental results show that the dispersion performance and lubrication performance of the V2O5-COFs coating material are consistent with the expected experimental results.

[0008] The beneficial effects of the present invention are as follows: the rolling oil for rolling pure molybdenum plates and molybdenum-rhenium alloy plates provided by the present invention has a low friction coefficient, good anti-oxidation performance, anti-corrosion performance and dispersion stability, and does not produce stratification and deposition after being placed for a long time ( Figure 5 ), it has excellent detergency and dispersibility, the lubricating oil produces little oil pollution during use, and the oil sample is clear and transparent ( Figure 5 ). During the cold rolling process, continuous lubrication can be achieved by spraying the rolling oil of the present invention once, with a large action range, longer action time, and reduced spraying times. Cold rolling using the rolling oil of the present invention for rolling pure molybdenum plates and molybdenum-rhenium alloy plates can, on the one hand, reduce rolling deformation resistance, reduce the bearing capacity of the equipment, and extend the service life of the equipment; on the other hand, it can reduce the number of rolling passes, increase the rolling rate, and greatly improve the production efficiency of the enterprise. BRIEF DESCRIPTION OF THE DRAWINGS

[0009] Figure 1 This is an example diagram of loading materials in a stainless steel high-temperature reactor in step 3 of preparing V2O5-COFs coating material in Example 1; Figure 2 This is a scanning electron microscope image of the V2O5-COFs coating material prepared in Example 1; Figure 3 The friction coefficient curve of the rolling oil prepared in Example 1 to Example 6; Figure 4The friction coefficient curve of the rolling oil prepared in Comparative Examples 1 to 6; Figure 5 This is a comparison chart of the rolling oil prepared in Example 4 before and after use. DETAILED DESCRIPTION

[0010] The present invention is further described below in conjunction with the embodiments, but the present invention is not limited in any way. Any changes or substitutions made based on the teachings of the present invention belong to the protection scope of the present invention.

[0011] A rolling oil for molybdenum and molybdenum alloy plates is composed of the following raw materials in parts by weight: 80.2-91.2 parts of base oil, 3-5 parts of V2O5-COFs coating material, 1-3 parts of oiliness agent, 0.5-1.0 parts of antioxidant, 1-3 parts of detergent, 1-3 parts of dispersant, 2-4 parts of rust inhibitor and 0.3-0.8 parts of anti-emulsifier.

[0012] The V2O5-COFs coating material is based on porous V2O5 nanospheres, the surface and inner structures of the nanospheres are COFs films, and the thickness of the film is 3-10 nm.

[0013] The particle size of the nanospheres is about 2 μm.

[0014] The preparation method of the V2O5-COFs coating material is as follows: 1) Preparation of V2O5 nanospheres; 2) Synthesize V2O5-COFs coating materials by surfactant template method.

[0015] In step 1), the preparation method of V2O5 nanospheres is as follows: a. Mix ammonium metavanadate, deionized water, sodium dodecylbenzene sulfonate and sodium ethylenediaminetetramethylenephosphonate and perform hydrothermal reaction in a hydrothermal reactor for 2-3 hours to obtain a light yellow solution; b. Add ethylene glycol, sodium di(2-ethylhexyl) succinate sulfonate and cetyltrimethylammonium bromide to the solution obtained in step a, react in water emulsion for 3-4 hours until flocculent precipitate appears, centrifuge, filter the precipitate, wash it several times with anhydrous ethanol, and then vacuum dry it, and then calcine it in a muffle furnace for 2-3 hours. The obtained bulk material is subjected to vibration ball milling to obtain V2O5 nanospheres; The mass ratio of ammonium metavanadate, sodium dodecylbenzenesulfonate, and sodium ethylenediaminetetramethylenephosphonate is 7:2:1; the mass ratio of ammonium metavanadate and deionized water is 1:10; the mass ratio of ethylene glycol, sodium di(2-ethylhexyl)succinate sulfonate, and hexadecyltrimethylammonium bromide is 8:1:1; the mass ratio of ethylene glycol and deionized water is 1:14.

[0016] In step a, the hydrothermal reaction temperature is 180-200°C; In step b, the hydrothermal reaction temperature is 100-120°C, the centrifugal speed is 10000-15000 rpm, and the centrifugal treatment time is 20-30 min; the calcination temperature is 600-800°C, and the heating rate is 10-20°C / min; the vibration ball milling time is set to 90-120 min, and the vibration frequency is 50 Hz.

[0017] The specific method of step 2) is as follows: three polytetrafluoroethylene beakers are placed in a polytetrafluoroethylene-lined stainless steel high-temperature reactor, and V2O5 nanospheres, a mixed solution of acetone, butyl laurate and dialdehyde polyethylene glycol, and a 25% tetraethylammonium hydroxide aqueous solution are placed in the beakers respectively. The V2O5 nanospheres are subjected to film-forming reaction in a pressurized steam environment for 4 to 5 hours. After the reaction is completed, water bath ultrasound is performed for 60 minutes, and finally vacuum drying is performed to obtain the V2O5-COFs coating material.

[0018] The volume ratio of acetone, butyl laurate, dialdehyde polyethylene glycol, tetraethylammonium hydroxide aqueous solution, and V2O5 nanospheres is 4:1:1:5:1; The heating temperature of the high temperature reactor is 220~240℃, the pressure is 12~15MPa; the water bath temperature is 70~80℃.

[0019] The base oil is transformer oil; the oiliness agent is any two or more of pentaerythritol oleate, pentaerythritol stearate and triethanolamine oleate; the antioxidant is any two or more of 2,6-di-tert-butyl-p-cresol, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, tris(2,4-di-tert-butylphenyl) phosphite; the detergent is any two or more of high base synthetic calcium sulfonate, high base alkyl salicylate calcium, high base cyclopentaneate calcium, high base alkyl phenol calcium sulfide; the dispersant is any one or more of polyisobutylene succinimide, polybutylene succinate, diene succinimide; the rust inhibitor is any two or more of sodium petroleum sulfonate, basic barium dinonylnaphthalene sulfonate, dodecenyl succinic acid; the anti-emulsifier is propylene oxide diamine polycondensate.

[0020] The present invention also provides a method for preparing the molybdenum and molybdenum alloy plate rolling oil, which is achieved by the following steps: (1) Add base oil and V2O5-COFs coating material in a stainless steel high-temperature reactor according to the weight ratio, stir at a speed of 600 rpm / min for 1-2 hours in the temperature range of 120-150°C, stop heating, and continue stirring until the temperature drops to 70-80°C; (2) Add other raw materials in the reactor in order according to weight, maintain the temperature of the reactor at 70-80°C, and stir at a stirring rate of 600-800 rpm / min for 1-2 hours to obtain the target molybdenum and molybdenum alloy plate rolling oil.

[0021] Example 1 Add 90g of deionized water to a beaker, use an electronic balance to weigh 7g of ammonium metavanadate, 2g of sodium dodecylbenzenesulfonate, and 1g of sodium ethylenediaminetetramethylenephosphonate, add them to the beaker and stir evenly, transfer the obtained mixed solution into a hydrothermal reactor and heat for 2h, set the heating temperature to 180°C, and take out a light yellow solution after the reaction is completed. Then add 5g of ethylene glycol, 0.625g of sodium di(2-ethylhexyl) succinate sulfonate, and 0.625g of hexadecyltrimethylammonium bromide to the mixed solution, transfer it into a hydrothermal reactor and heat for 3h, set the heating temperature to 120°C, and after the reaction is completed, the solution becomes turbid and flocculent precipitation appears, and is placed in a centrifuge for centrifugal treatment, the speed is set to 12000rpm / min, the centrifugation time is 20min, the precipitate is separated and washed several times with anhydrous ethanol, and the precipitate is vacuum dried. The obtained precipitate is put into a quartz crucible and placed in a muffle furnace for calcination. The preset temperature of the muffle furnace is set to 600°C, the heating rate is set to 10°C / min, the calcination time is 2h, and blocky V2O5 balls are obtained. The blocky V2O5 balls are ground using a high-frequency vibration ball mill. The vibration frequency is set to 50Hz and the vibration time is 90min. After ball milling twice, the ball mill is allowed to stand for 6h and the V2O5 nanospheres are taken out.

[0022] Weigh 30ml acetone, 0.855g dibutyl dilaurate and 0.2mg dialdehyde polyethylene glycol, mix well and put into a polytetrafluoroethylene beaker, add 65ml aqueous tetraethylammonium hydroxide (TEAOH, 25%) in another beaker, then put the beaker into a stainless steel high-temperature reactor lined with polytetrafluoroethylene, weigh 2g of the obtained V2O5 nanospheres and add them into the reactor, the heating temperature is 240℃, the pressure is 15MPa, the reaction time is 4h, and the film-forming reaction is carried out in a steam environment. After the reaction is completed, water bath ultrasound is carried out for 60min, and vacuum drying is carried out to obtain the V2O5-COFs coating material.

[0023] Weigh 85.8 parts of transformer oil by weight, add 3 parts of V2O5-COFs coating material, put the raw materials into a stainless steel high-temperature reactor, raise the reactor temperature to 150°C, stir at 600rpm / min, stir for 1h, stop heating, continue stirring and wait for the temperature to drop to about 80°C. Then add 1.54 parts of pentaerythritol oleate and 0.66 parts of pentaerythritol stearate to add oiliness agent, 0.4 parts of antioxidant 1010 and 0.4 parts of antioxidant 168 to add antioxidant, 1.1 parts of high base synthetic calcium sulfonate and 1.1 parts of high base calcium salicylate to add detergent, 2.2 parts of polyisobutylene succinimide, 1.6 parts of petroleum calcium sulfonate and 1.6 parts of basic barium dinonylnaphthalene sulfonate to add rust inhibitor, and 0.6 parts of propylene oxide diamine polymer to the reactor. The reactor temperature was set at 80°C and stirred at a speed of 600 rpm / min for 1 h to obtain the final rolling oil product.

[0024] Example 2 85.4 parts of transformer oil and 3.4 parts of V2O5-COFs coating material prepared in Example 1 were weighed according to weight, and the raw materials were placed in a stainless steel high-temperature reactor. The reactor temperature was raised to 150° C., the stirring speed was 600 rpm / min, and the stirring time was 1 hour. At this time, the heating process was stopped, and stirring was continued until the temperature dropped to about 80° C. Then, 1.54 parts of pentaerythritol oleate and 0.66 parts of pentaerythritol stearate were added in combination with an oiliness agent, 0.4 parts of antioxidant 1010 and 0.4 parts of antioxidant 168 were added in combination with an antioxidant, 1.1 parts of high-base synthetic calcium sulfonate and 1.1 parts of high-base calcium salicylate were added in combination with a detergent, 2.2 parts of polyisobutylene succinimide, 1.6 parts of petroleum calcium sulfonate and 1.6 parts of basic barium dinonylnaphthalene sulfonate were added in combination with a rust inhibitor, and 0.6 parts of propylene oxide diamine polymer were added in the reactor. The reactor temperature was set at 80°C and stirred at a speed of 600 rpm / min for 1 h to obtain the final rolling oil product.

[0025] Example 3 85 parts of transformer oil and 3.8 parts of V2O5-COFs coating material prepared in Example 1 were weighed according to weight, and the raw materials were placed in a stainless steel high-temperature reactor. The reactor temperature was raised to 150° C., the stirring speed was 600 rpm / min, and the stirring time was 1 hour. At this time, the heating process was stopped, and stirring was continued until the temperature dropped to about 80° C. Then, 1.54 parts of pentaerythritol oleate and 0.66 parts of pentaerythritol stearate were added in combination with an oiliness agent, 0.4 parts of antioxidant 1010 and 0.4 parts of antioxidant 168 were added in combination with an antioxidant, 1.1 parts of high-base synthetic calcium sulfonate and 1.1 parts of high-base calcium salicylate were added in combination with a detergent, 2.2 parts of polyisobutylene succinimide, 1.6 parts of petroleum calcium sulfonate and 1.6 parts of basic barium dinonylnaphthalene sulfonate were added in combination with a rust inhibitor, and 0.6 parts of propylene oxide diamine polymer were added in the reactor. The reactor temperature was set at 80°C and stirred at a speed of 600 rpm / min for 1 h to obtain the final rolling oil product.

[0026] Example 4 84.6 parts of transformer oil and 4.2 parts of V2O5-COFs coating material prepared in Example 1 were weighed according to weight, and the raw materials were placed in a stainless steel high-temperature reactor. The reactor temperature was raised to 150° C., the stirring speed was 600 rpm / min, and the stirring time was 1 hour. At this time, the heating process was stopped, and stirring was continued until the temperature dropped to about 80° C. Then, 1.54 parts of pentaerythritol oleate and 0.66 parts of pentaerythritol stearate were added in combination with an oiliness agent, 0.4 parts of antioxidant 1010 and 0.4 parts of antioxidant 168 were added in combination with an antioxidant, 1.1 parts of high-base synthetic calcium sulfonate and 1.1 parts of high-base calcium salicylate were added in combination with a detergent, 2.2 parts of polyisobutylene succinimide, 1.6 parts of petroleum calcium sulfonate and 1.6 parts of basic barium dinonylnaphthalene sulfonate were added in combination with a rust inhibitor, and 0.6 parts of propylene oxide diamine polymer were added in the reactor. The reactor temperature was set at 80°C and stirred at a speed of 600 rpm / min for 1 h to obtain the final rolling oil product.

[0027] Example 5 84.2 parts of transformer oil and 4.6 parts of V2O5-COFs coating material prepared in Example 1 were weighed according to weight, and the raw materials were placed in a stainless steel high-temperature reactor. The reactor temperature was raised to 150° C., the stirring speed was 600 rpm / min, and the stirring time was 1 hour. At this time, the heating process was stopped, and stirring was continued until the temperature dropped to about 80° C. Then, 1.54 parts of pentaerythritol oleate and 0.66 parts of pentaerythritol stearate were added in combination with an oiliness agent, 0.4 parts of antioxidant 1010 and 0.4 parts of antioxidant 168 were added in combination with an antioxidant, 1.1 parts of high-base synthetic calcium sulfonate and 1.1 parts of high-base calcium salicylate were added in combination with a detergent, 2.2 parts of polyisobutylene succinimide, 1.6 parts of petroleum calcium sulfonate and 1.6 parts of basic barium dinonylnaphthalene sulfonate were added in combination with a rust inhibitor, and 0.6 parts of propylene oxide diamine polymer were added in the reactor. The reactor temperature was set at 80°C and stirred at a speed of 600 rpm / min for 1 h to obtain the final rolling oil product.

[0028] Example 6 83.8 parts of transformer oil and 5 parts of V2O5-COFs coating material prepared in Example 1 were weighed according to weight, and the raw materials were placed in a stainless steel high-temperature reactor. The reactor temperature was raised to 150° C., the stirring speed was 600 rpm / min, and the stirring time was 1 hour. At this time, the heating process was stopped, and stirring was continued until the temperature dropped to about 80° C. Then, 1.54 parts of pentaerythritol oleate and 0.66 parts of pentaerythritol stearate were added in combination with an oiliness agent, 0.4 parts of antioxidant 1010 and 0.4 parts of antioxidant 168 were added in combination with an antioxidant, 1.1 parts of high-base synthetic calcium sulfonate and 1.1 parts of high-base calcium salicylate were added in combination with a detergent, 2.2 parts of polyisobutylene succinimide, 1.6 parts of petroleum calcium sulfonate and 1.6 parts of basic barium dinonylnaphthalene sulfonate were added in combination with a rust inhibitor, and 0.6 parts of propylene oxide diamine polymer were added in the reactor. The reactor temperature was set at 80°C and stirred at a speed of 600 rpm / min for 1 h to obtain the final rolling oil product.

[0029] Comparative Example 1 The difference between this comparative example and Example 4 is that no V2O5-COFs coating material is added to the rolling oil raw material, and other raw materials and preparation methods are the same as those in Example 4.

[0030] Comparative Example 2 The difference between this comparative example and Example 4 is that V2O5 nanospheres are used instead of V2O5-COFs coating materials as raw materials, and other raw materials and preparation methods are the same as those in Example 4.

[0031] Comparative Example 3 The difference between this comparative example and Example 4 is that COFs film is used instead of V2O5-COFs coating material as raw material, and other raw materials and preparation methods are the same as those in Example 4.

[0032] The preparation method of COFs film is as follows: 0.15g dibutyl dilaurate and 0.2g dialdehyde polyethylene glycol are dissolved in a polar solvent mixture composed of acetone and ethanol, 3ml of the mixed solution is dropped on a 30mm×30mm clean glass substrate, three such glass substrates are placed in a stainless steel high-temperature reactor, and 10ml of tetraethylammonium hydroxide (TEAOH, 25%) aqueous solution is placed at the same time. The reactor is heated to 150°C, the pressure is 10MPa, and the reaction time is 12h. After the conversion is completed, a layer of COFs film is evenly covered on the surface of the glass substrate. The COFs film is scraped off the glass substrate and subjected to water bath ultrasound for 60min to obtain a uniformly dispersed COFs film.

[0033] Comparative Example 4 This comparative example uses a certain anti-wear hydraulic oil on the market, which can be used in the cold rolling process, and compares the tribological properties with the rolling oil product prepared in Example 4.

[0034] Comparative Example 5 Compared with Example 4, the amount of V2O5-COFs coating material added in this comparative example remains unchanged at 4.2 parts, and the amount of other functional additives added is increased to twice the content of Example 4, that is, 73.2 parts of base oil, 3.08 parts of pentaerythritol oleate and 1.32 parts of pentaerythritol stearate composite oiliness agent, 0.8 parts of antioxidant 1010 and 0.8 parts of antioxidant 168 composite added antioxidant, 2.2 parts of high base synthetic calcium sulfonate and 2.2 parts of high base calcium salicylate composite added detergent, 4.4 parts of polyisobutylene succinimide, 3.2 parts of petroleum calcium sulfonate and 3.2 parts of basic barium dinonylnaphthalene sulfonate, and 1.2 parts of propylene oxide diamine polymer are added to the reactor.

[0035] Comparative Example 6 Compared with Example 4, the amount of V2O5-COFs coating material added in this comparative example remains unchanged at 4.2 parts, and the amount of other functional additives added is reduced to 1 / 2 of the content in Example 4, that is, 90.4 parts of base oil, 0.77 parts of pentaerythritol oleate and 0.33 parts of pentaerythritol stearate composite oiliness agent, 0.1 parts of antioxidant 1010 and 0.1 parts of antioxidant 168 composite added antioxidant, 0.55 parts of high base synthetic calcium sulfonate and 0.55 parts of high base calcium salicylate composite added detergent, 1.1 parts of polyisobutylene succinimide, 0.8 parts of petroleum calcium sulfonate and 0.8 parts of basic barium dinonylnaphthalene sulfonate, and 0.3 parts of propylene oxide diamine polymer are added to the reactor.

[0036] Test Example 1 Performance Test of Rolling Oil Prepared in Examples 1-6 1. Analysis of rolling oil friction performance The rolling oil prepared in Examples 1 to 6 and Comparative Examples 1 to 6 were tested for performance, and the detection method was as follows: a four-ball friction tester MS-10J was used to test the maximum no-seizure load (PB) and long-term friction coefficient (COF). The standard test ball was a GCr15 bearing steel ball with a specification of 12.700 mm ± 0 (-0.2) μm. The implementation standard was GB / T3142-2019 "Determination of Lubricant Load-bearing Capacity Four-ball Method", and the fixed parameters were: load 392 N, speed 1200 rpm / min, and running time 60 min. Before the experiment, anhydrous ethanol and petroleum ether mixed solvent was used to ultrasonically clean the standard test ball, oil cup and other experimental equipment, install the sample according to the operating instructions, load the test rolling oil, start the experimental machine, and record the relevant friction curve; the experiments of Examples 1-6 and Comparative Examples 1-6 were carried out respectively according to the same operating steps.

[0037] Result analysis: from Figure 3 It can be seen that in Examples 1 to 6, additives and V2O5-COFs coating materials are added in the same proportion. When the content of other functional additives remains unchanged, the amount of coating materials added is changed to determine the optimal amount of coating materials added. It can be seen from the figure that the amount of coating materials added in Example 1 is small, and the initial friction coefficient is maintained at a low level. As the friction experiment proceeds, the friction coefficient gradually increases, indicating that the friction film formed at this time is constantly consumed. When entering the stable friction and wear stage, the friction coefficient of the contact surface gradually fluctuates in a large range, indicating that it is difficult for the coating material to form a complete friction film at this time. As the experiment proceeds, the friction surface is constantly in contact with the friction pair, causing the surface wear rate to increase. As the content of the coating material increases, the average friction coefficient gradually decreases. From Examples 2 and 3, it can be observed that the friction coefficient continues to decrease as the friction experiment proceeds. At about 2000s, it enters the stable friction and wear stage, at which time the friction coefficient fluctuates. After that, the friction coefficient still fluctuates within a stable range, indicating that as the content of the coating material increases, a complete friction film can still be formed in the stable wear stage to reduce the wear of the substrate. The friction coefficient of Example 4 is the lowest. When the friction experiment reaches the stable wear stage, the average friction coefficient is 0.041. At this time, the amount of coating material added is the optimal ratio, and the running-in period between the substrate and the friction pair is short, and the stable wear stage can be entered quickly, thereby maintaining a low friction coefficient. Further increasing the content of coating material and additives found that the average friction coefficient will gradually increase, indicating that the amount of coating material added will affect the dispersion stability of the oil, and excessive coating material will cause accumulation, which will affect the friction coefficient.

[0038] from Figure 4It can be seen that Comparative Example 1 is a rolling oil without adding coating materials. At this time, it is difficult for the lubricant to form a continuous lubricating film. In the early stage of the friction stage, it relies on functional additives to play a role. As the friction experiment proceeds, the friction coefficient fluctuates violently, resulting in a continuous increase in the wear rate of the substrate. Comparative Examples 2 and 3 are only adding a single material, and the average friction coefficient is significantly reduced, but the friction coefficient curve fluctuates violently. It can be observed that Comparative Example 2 is a friction curve with V2O5 nanospheres added. Since the nanospheres are difficult to form a stable adsorption effect on the friction surface, its initial friction coefficient increases sharply. Due to the adsorption film formed by the rupture of some nanospheres, the friction coefficient is reduced. Comparative Example 3 is a COFs film material added. Since the COFs film can be adsorbed on the substrate surface, the friction coefficient fluctuates within a stable range, but the extreme pressure value of the COFs film is not high, and it is difficult to withstand a large load. Therefore, as the friction experiment proceeds, the COFs film ruptures and the process of re-adsorption occurs. Comparative Example 4 is a selected anti-wear hydraulic oil on the market. The friction and wear stage of this product is stable and can meet the use of rolling conditions. The average friction coefficient of commercially available anti-wear hydraulic oil is 0.075. The rolling oil prepared by the present invention has a lower friction coefficient and has a better effect on improving the surface quality of the plate during the rolling process. Comparative Example 5 keeps the coating material content unchanged and increases the content of other functional additives. By comparing the examples, it can be found that the increase in the content of other additives will increase the friction coefficient, but the friction and wear process is still very stable, and the running-in period is reached at the beginning of the friction experiment. Comparative Example 6 keeps the coating material unchanged and reduces the content of other functional additives. The results show that the friction coefficient curve fluctuates violently, indicating that the content of other functional additives also has an impact on the friction process.

[0039] 2. Analysis of physical and chemical properties of rolling oil Table 1 Physical and chemical properties test data of rolling oil prepared in Example 4 Result analysis: As can be seen from Table 1, the rolling oil prepared in Example 4 has a high kinematic viscosity and open flash point, indicating that the ability to form an oil film at the lubricated part is strong, which is conducive to maintaining the lubrication effect under high speed and high load conditions; the high open flash point indicates that the rolling oil has good thermal stability and oxidation stability, is not easy to decompose and deteriorate, and prolongs the service life of the lubricating oil. In addition, the friction coefficient of the prepared rolling oil is significantly lower than that of the commercially available anti-wear hydraulic oil, which can roll thinner plates on the one hand and improve the surface quality of the plates on the other hand. Compared with the commercially available anti-wear hydraulic oil, the rolling oil prepared in Example 4 can meet the requirements of the cold rolling process of molybdenum alloys.

[0040] 3. The rolling oil prepared in Example 4 and the commercially available anti-wear hydraulic oil were used to test pure molybdenum and molybdenum-rhenium alloy. The cold rolling was carried out, and the rolling parameters are shown in Table 2.

[0041] Table 2 Comparison of industrial application data of rolling oil Result analysis: From Table 2, it can be seen that the comparison results of actual use show that the currently available anti-wear hydraulic oil can guarantee basic production efficiency. The rolling oil prepared by Example 4 can significantly reduce the number of times the lubricating oil is sprayed during the rolling process, increase the rolling speed, and thus improve production efficiency.

Claims

1. A rolling oil for molybdenum and molybdenum alloy plates, characterized in that: The invention is composed of the following raw materials in parts by weight: 80.2-91.2 parts of base oil, 3-5 parts of V2O5-COFs coating material, 1-3 parts of oiliness agent, 0.5-1.0 parts of antioxidant, 1-3 parts of detergent, 1-3 parts of dispersant, 2-4 parts of rust inhibitor and 0.3-0.8 parts of anti-emulsifier.

2. The rolling oil for molybdenum and molybdenum alloy sheets according to claim 1, characterized in that: The V2O5-COFs coating material is based on porous V2O5 nanospheres, the surface and inner structures of the nanospheres are COFs films, and the thickness of the film is 3-10 nm.

3. The rolling oil for molybdenum and molybdenum alloy sheets according to claim 2, characterized in that: The particle size of the nanospheres is about 2 μm.

4. The rolling oil for molybdenum and molybdenum alloy sheets according to claim 1, characterized in that: The preparation method of the V2O5-COFs coating material is as follows: 1) Preparation of V2O5 nanospheres; 2) Synthesize V2O5-COFs coating materials by surfactant template method.

5. The rolling oil for molybdenum and molybdenum alloy sheets according to claim 4, characterized in that: In step 1), the preparation method of V2O5 nanospheres is as follows: a. Mix ammonium metavanadate, deionized water, sodium dodecylbenzene sulfonate and sodium ethylenediaminetetramethylenephosphonate and perform hydrothermal reaction in a hydrothermal reactor for 2-3 hours to obtain a light yellow solution; b. Add ethylene glycol, sodium di(2-ethylhexyl) sulfosuccinate and cetyltrimethylammonium bromide to the solution obtained in step a, react in water emulsion for 3-4 hours until flocculent precipitate appears, centrifuge, filter the precipitate, wash it several times with anhydrous ethanol, and then vacuum dry it, and then calcine it in a muffle furnace for 2-3 hours. The obtained bulk material is subjected to vibration ball milling to obtain V2O5 nanospheres; The mass ratio of ammonium metavanadate, sodium dodecylbenzenesulfonate, and sodium ethylenediaminetetramethylenephosphonate is 7:2:1; the mass ratio of ammonium metavanadate and deionized water is 1:10; the mass ratio of ethylene glycol, sodium di(2-ethylhexyl)succinate sulfonate, and hexadecyltrimethylammonium bromide is 8:1:1; the mass ratio of ethylene glycol and deionized water is 1:

14.

6. The rolling oil for molybdenum and molybdenum alloy sheets according to claim 5, characterized in that: In step a, the hydrothermal reaction temperature is 180-200°C; In step b, the hydrothermal reaction temperature is 100-120°C, the centrifugal speed is 10000-15000 rpm, and the centrifugal treatment time is 20-30 min; the calcination temperature is 600-800°C, and the heating rate is 10-20°C / min; the vibration ball milling time is set to 90-120 min, and the vibration frequency is 50 Hz.

7. The rolling oil for molybdenum and molybdenum alloy sheets according to claim 4, characterized in that: The specific method of step 2) is as follows: three polytetrafluoroethylene beakers are placed in a polytetrafluoroethylene-lined stainless steel high-temperature reactor, and V2O5 nanospheres, a mixed solution of acetone, butyl laurate and dialdehyde polyethylene glycol, and a 25% tetraethylammonium hydroxide aqueous solution are placed in the beakers respectively. The V2O5 nanospheres are subjected to film-forming reaction in a pressurized steam environment for 4 to 5 hours. After the reaction is completed, water bath ultrasound is performed for 60 minutes, and finally vacuum drying is performed to obtain the V2O5-COFs coating material.

8. The rolling oil for molybdenum and molybdenum alloy sheets according to claim 7, characterized in that: The volume ratio of acetone, butyl laurate, dialdehyde polyethylene glycol, tetraethylammonium hydroxide aqueous solution, and V2O5 nanospheres is 4:1:1:5:1; The heating temperature of the high temperature reactor is 220~240℃, the pressure is 12~15MPa; the water bath temperature is 70~80℃.

9. The rolling oil for molybdenum and molybdenum alloy sheets according to claim 1, characterized in that: The base oil is transformer oil; the oiliness agent is any two or more of pentaerythritol oleate, pentaerythritol stearate and triethanolamine oleate; the antioxidant is any two or more of 2,6-di-tert-butyl-p-cresol, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, tris(2,4-di-tert-butylphenyl) phosphite; the detergent is any two or more of high base synthetic calcium sulfonate, high base alkyl salicylate calcium, high base cyclopentaneate calcium, high base alkyl phenol calcium sulfide; the dispersant is any one or more of polyisobutylene succinimide, polybutylene succinate, diene succinimide; the rust inhibitor is any two or more of sodium petroleum sulfonate, basic barium dinonylnaphthalene sulfonate, dodecenyl succinic acid; the anti-emulsifier is propylene oxide diamine polycondensate.

10. The method for preparing rolling oil for molybdenum and molybdenum alloy sheets according to claim 1, characterized in that: To do this, follow these steps: (1) Add base oil and V2O5-COFs coating material in a stainless steel high-temperature reactor according to the weight ratio, stir at a speed of 600 rpm / min for 1-2 hours in the temperature range of 120-150°C, stop heating, and continue stirring until the temperature drops to 70-80°C; (2) Add other raw materials in the reactor in order according to weight, maintain the temperature of the reactor at 70-80°C, and stir at a stirring rate of 600-800 rpm / min for 1-2 hours to obtain the target molybdenum and molybdenum alloy plate rolling oil.